Botswana : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2014)
KEY ISSUES Setting: The seeds of good governance and prudent macroeconomic and natural resources management planted by the Botswana authorities paid off with an impressive increase in the GDP per capita during the last three decades. However, as in many other small middle-income countries (SMICs) in the region, trend growth has softened in recent years, reflecting the decline in the contribution of total factor productivity (TFP) to growth which calls for policies to reduce structural bottlenecks in the economy. Current conditions and outlook: Botswana's economy remains broadly internally and externally balanced and the authorities' near-term macroeconomic policy mix is appropriate. Output growth is expected to slowdown in 2014 reflecting partly weaknesses in the non-mineral sector, while inflation is expected to remain within the Bank of Botswana's (BoB) medium-term objective range of 3-6 percent. Fiscal policy: Staff supports the FY2014/15 budget, which reins in unproductive current spending, while protecting growth-promoting capital spending. Achieving medium-term fiscal consolidation objectives adopted in the budget, would require articulating concrete measures to reduce the wage bill relative to GDP and broaden the revenue base. Financial sector development: Botswana's banking system is well-capitalized and profitable with relatively low nonperforming loans. Although from a low base, credit growth to households continues to expand at a high rate, which poses potential vulnerabilities for the financial sector. Thus, staff recommends that macro prudential measures be considered to temper the rate of growth of household borrowing. In this context, staff welcomes the government's emphasis on enhancing greater financial deepening and inclusion, while preserving the stability of the financial system. Reinvigorating growth: Returning to an era of strong growth and accelerating Botswana's convergence to higher income levels would require policies to reinvigorate TFP growth. These include improving the quality of public spending, notably in public investment projects and education to ensure the transformation of diamond wealth into sustainable assets. The authorities' efforts to improve the country's competitiveness, including through reducing the regulatory burden on firms, is also welcomed. Past advice: There is broad agreement between the Fund and the authorities on the macroeconomic policy stance and structural reform policy priorities. Consistent with staff's advice, the FY 2014/15 budget outlined a framework to reduce the burden of loss- making state-owned enterprises on fiscal resources and propel them toward commercial viability. Furthermore, the budget includes medium-term projections of government accounts, as recommended by staff during past consultations. However, progress towards reducing the wage bill relative to GDP remains modest.